Sustainable materials for novel food packaging based on alginate, methylcellulose and glycerol films functionalized with gallic acid - Francisco Javier Leyva-Jiménez; Carlos Abellán-Dieguez; Rodrigo Oliver-Simancas; Antonio M. Rodríguez-García; M. Elena Alañón (Future Foods, 2024)
In the last years, new sustainable materials have been explored as plastic replacement in food industry. With the objective of developing sustainable active materials for food packaging, polysaccharide-based films: alginate, methylcellulose and glycerol-based films (ALG-MC-GLY (65:30:5)) were formulated and functionalized with different concentration of gallic acid (0.1, 0.5 and 0.8 % w/v). The mechanical, physicochemical, optical and functional properties of the films were evaluated. The incorporation of gallic acid resulted in films less resistant to tensile stress and less elastic, exhibiting reduced water vapor permeability. The physico-mechanical characterization was corroborated by FTIR spectra, HRSEM imaging and BET analyses, which demonstrated the interactions between the polymeric chains and gallic acid through localized hydrogen bonding, leading to denser structures with increased brittleness at higher concentrations of gallic acid. Moreover, the films functionalized with gallic acid displayed enhanced antioxidant properties in a concentration-dependent manner. These findings suggest that the ALG-MC-GLY based films loaded with gallic acid hold significant promise as alternative active food packaging materials.